Perception of PJOK Teachers on Readiness in The Implementation of The Independent Curriculum - Ridwan Nuriman; Dini Rosdiani; Yudi Hidayat (Journal of Physical and Outdoor Education, 2026)
This study aims to find out the perception of Physical Education, Sports, and Health (PJOK) teachers on the readiness to implement the Independent Curriculum at the junior high school level. The Independent Curriculum demands a change in the learning paradigm that emphasizes differentiated learning, diagnostic assessments, and strengthening student character through the Pancasila Student Profile. In this context, PJOK teachers have their own challenges in adjusting learning methods in accordance with the principles of this new curriculum. This study uses a quantitative descriptive approach with questionnaire instruments distributed to PJOK teachers in several public and private schools. The results of the study show that most teachers have a fairly good initial understanding of the basic principles of the Independent Curriculum, but still feel that they are not fully prepared in terms of planning, implementation, and evaluation of learning. Factors that affect the unpreparedness include the lack of specific training, limited facilities, and suboptimal support from the school. These findings show the need to strengthen teacher capacity through more systematic training and more concrete policy support so that the implementation of the Independent Curriculum in PJOK subjects can run optimally.